Effect of Proportion of Home and External Scrap on the Mechanical Properties of Recycled PVC: A Comparative Study - M. Jalal Uddin; Fahmida Gulshan; ASW Kurny (Journal of Mechanical Engineering and Sciences, 2015)
Raw material powder mixtures have been prepared with PVC resin, unplasticized polyvinylchloride (uPVC) scrap and additives. A twin screw extruder has been used to make pipe for sample preparation from the mixture. Domestic and external uPVC scrap were formulated and blended with PVC resin to form melt compound. Domestic samples designated as DS-10, DS-20, DS-30, DS-40, DS-50 and DS-100 have been prepared by blending 10, 20, 30, 40, and 50 phr and 100% uPVC domestic scrap with PVC resin and various additives, followed by extrusion, flattening and machining. Following a similar procedure, external samples such as ES-10, ES-20, ES-30, ES-40, ES-50 and ES-100 have been prepared using external uPVC scrap. The effects of the proportions of uPVC scrap in the raw material mix on the mechanical properties such as break stress (BS), % elongation at break, flexural yield strength [1], impact strength (IS) and Shore hardness were investigated. The maximum decrease in break stress is 11.40% for 20 phr domestic scrap, while in samples containing external scrap this decrease is 15.71% for 40 phr scrap. The minimum and maximum reduction in IS values of DS are recorded 1.0% for DS-10 and 27.4% for DS-40, respectively, whereas the minimum and maximum decrease in IS values of ES recorded are 9.6% for ES-10 and 39.2% for ES-50, respectively. The minimum and maximum increase in hardness values of DS are recorded as 0.07% for DS-40 and 2.8% for DS-10, respectively, whereas the minimum and maximum reduction in hardness values of ES are recorded as 1.2% for ES-50 and 2.2% for ES-20, respectively. The mechanical properties of samples were found to deteriorate with increasing quantity of scrap in the raw material mix, the effects of external scrap being more prominent.